2010
DOI: 10.1007/s10577-010-9139-6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species chromosome painting in bats from Madagascar: the contribution of Myzopodidae to revealing ancestral syntenies in Chiroptera

Abstract: The chiropteran fauna of Madagascar comprises eight of the 19 recognized families of bats, including the endemic Myzopodidae. While recent systematic studies of Malagasy bats have contributed to our understanding of the morphological and genetic diversity of the island's fauna, little is known about their cytosystematics. Here we investigate karyotypic relationships among four species, representing four families of Chiroptera endemic to the Malagasy region using cross-species chromosome painting with painting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…This fission separates the HSA16 homologous segment from the HSA7-5 homologous segment, as has been shown for Hipposideros larvatus [Volleth et al, 2002]. Fission of the MMY8 homolog has also been found in Myzopoda [Richards et al, 2010]. Painting with human probes is needed to clarify whether the breakpoint in Myzopoda is similar to that in Rhinolophoidea.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 75%
See 4 more Smart Citations
“…This fission separates the HSA16 homologous segment from the HSA7-5 homologous segment, as has been shown for Hipposideros larvatus [Volleth et al, 2002]. Fission of the MMY8 homolog has also been found in Myzopoda [Richards et al, 2010]. Painting with human probes is needed to clarify whether the breakpoint in Myzopoda is similar to that in Rhinolophoidea.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 75%
“…Only these chromosomal features that have been found in more than 1 taxon up to date are presented in table 5 (numbers 1-19). Closer examination and recent results revealed that some characters, which have been previously reported to be shared features [Volleth et al, 2002;Mao et al, 2008;Richards et al, 2010], represent in fact 2 different characters (numbers 20-23). Therefore, we separated these features into 'a' and 'b' in table 5 .…”
Section: Phylogenetic Relationshipsmentioning
confidence: 81%
See 3 more Smart Citations